COVID-19 AND INTERNET OF THINGS: A STUDY OF ENTERPRISE AND CONSUMER CONDITION DURING LOCKDOWN - Dr. Ashutosh Singh, Mr. Brijesh Kishore Goswami, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The global pandemic of COVID-19 has had a big effect on our society in a number of respects. COVID-19 is now contamination impacting many countries around the world. The sickness and ensuing disintegrate also impacted various industries, including MSME, retail, civil aviation, agriculture and the personal region. This paper describes the prevailing impact of COVID-19 on the global IoT supply chain and the feasible affect that COVID19 may have at the IoT customer / demand aspect. This take a look at would illustrate how this pandemic is leading agencies to call for extra duty, Capex and rethink supply chains. we might additionally address how IoT systems "music & trace," "faraway resource manage" and precise instances of healthcare usage benefit from such changing demands earlier than and all through the crisis. last but now not least, it'll reflect at the results of the Covid-19 platform, the results of self safety and the results on public and companies.